The Effect of Crossword Puzzle Learning Strategy To The Learning Competencies of Students At Padang Public Junior High School 14 - Siti Verani Fauziah; Helendra Helendra; Sa'diatul Fuadiyah; Ramadhan Sumarmin (ATRIUM PENDIDIKAN BIOLOGI, 2020)
One feature of the 2013 Curriculum is that there is active interaction between students and teachers. Learning becomes more student-centered rather than teacher-centered. The results of observations of researchers at SMP 14 Padang showed that the teacher still applied direct instruction learning. So that many students are less active and still have low learning competencies. This study aims to see the effect of applying the crossword puzzle learning strategy to the learning competencies of students in excretory system material at Padang Public Junior High  School 14. The population in this study were all class VIII in SMP 14 Padang which were registered in the even semester of the 2018/2019 academic year totaling eight classes. Sampling was done using purposive sampling technique, which was chosen as the research sample was class VIII.4 as the experimental class and class VIII.5 as the control class. The research instrument used was in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. The hypothesis in this study was tested using the t test. The t-test results revealed that the knowledge competencies t count> t table (5.04> 1.67), the competencies of the t-test attitude> t table (4.57> 1.67) and the skills competency t count> t table (4.35> 1, 67). This shows that the hypothesis is accepted. So it can be concluded that the application of the crossword puzzle learning strategy can improve the learning competencies of class VIII students on excretory system material at Padang Public Junior High School 14One feature of the 2013 Curriculum is that there is active interaction between students and teachers. Learning becomes more student-centered rather than teacher-centered. The results of observations of researchers at SMP 14 Padang showed that the teacher still applied direct instruction learning. So that many students are less active and still have low learning competencies. This study aims to see the effect of applying the crossword puzzle learning strategy to the learning competencies of students in excretory system material at Padang Public Junior High  School 14. The population in this study were all class VIII in SMP 14 Padang which were registered in the even semester of the 2018/2019 academic year totaling eight classes. Sampling was done using purposive sampling technique, which was chosen as the research sample was class VIII.4 as the experimental class and class VIII.5 as the control class. The research instrument used was in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. The hypothesis in this study was tested using the t test. The t-test results revealed that the knowledge competencies t count> t table (5.04> 1.67), the competencies of the t-test attitude> t table (4.57> 1.67) and the skills competency t count> t table (4.35> 1, 67). This shows that the hypothesis is accepted. So it can be concluded that the application of the crossword puzzle learning strategy can improve the learning competencies of class VIII students on excretory system material at Padang Public Junior High School 14.